HUBUNGAN KELINCAHAN DAN DAYA TAHAN DENGANHASIL DRIBBLE BOLA BASKET PADA TIM PUTRA SMAN 6 PEKANBARU - Afdal Windra utama; Ramadi Ramadi; Kristi August (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research is always loose control of the ball possession, too difficult to break through the opponent's defense, too difficult to break through the opponent's defense, failed in transition offens, excessive fatigue are experienced athletes so many athletes who experience muscle cramps. The purpose of this research was to determine whether there is a correlation agility and endurance with the results dribble in the men's basketball team SMAN 6 Pekanbaru. The population in this study are all basketball players SMAN 6 Pekanbaru totaling 12 people. A sampling technique that the overall population (total sampling). Instruments used in this research is dooging test run, which aims to measure the agility then Bleep Test to measure the durability and zig-zag Dribbling which aims to find out how big the dribble of the sample used. After that, if the statistical data, to test for normality with lilifors test at significant level a0,05. Based on the research results, it can be concluded as follows. From the results obtained agility has a correlationwith the results dribbling a basketball on the men's team SMAN6 Pekanbaru in because, where rhitung at significant level α (0,05) = 0.602 means rhitung (0.621)> rtab (0.602), of the results obtained there is a relationship between durability with the results dribble in because, where rtab at significant level α (0,05) = 0.602 means rhitung (0.669)> rtab (0.602), There is a meaningful relationship together between agility and endurance with the results of dribbling the ball basketball on students SMAN6 Pekanbaru in because rhitung (0694)> rtab (0602).Keywords: Agility, Endurance, Dribbling Results.